1993
DOI: 10.1111/j.1365-2133.1993.tb03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with psoriasis often have increased serum levels of IgA antibodies to gliadin

Abstract: It was recently observed that in six patients with psoriasis and one with palmoplantar pustulosis, with newly discovered gluten intolerance, a gluten-free diet had a remarkable effect on the skin lesions. This prompted us to undertake a screening investigation to discover whether increased levels of serum antibodies to gliadin are more common in patients with psoriasis than in healthy persons. IgA and IgG antibodies to gliadin (IgA AGA and IgG AGA) were quantified by a micro-ELISA method. Out of 302 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 9 publications
3
65
1
5
Order By: Relevance
“…A link between psoriasis and CD was proposed by early studies [27,28,29,30] and controverted by others [31]. The prevalence of CD increases 2-4-fold in the population with psoriasis.…”
Section: Mucocutaneous Manifestations Of CDmentioning
confidence: 99%
“…A link between psoriasis and CD was proposed by early studies [27,28,29,30] and controverted by others [31]. The prevalence of CD increases 2-4-fold in the population with psoriasis.…”
Section: Mucocutaneous Manifestations Of CDmentioning
confidence: 99%
“…El cálculo del tamaño de la muestra se realizó considerando una prevalencia estimada de 10% (p =0,1) de la asociación entre enfermedad celíaca y psoriasis 16,17,19 , con un nivel de confianza de 95% y un tamaño máximo de error de 4%, lo que dio una cifra de 79 casos.…”
Section: Pacientes Y Métodosunclassified
“…En nuestra serie, sólo 6 pacientes tuvieron AGA positivo (6/26), por debajo de lo encontrado en estudios de Michaelsson y cols 16 ; sin embargo, nuestras cifras están de acuerdo con otras publicaciones 18,19 (Tabla 4).…”
Section: N V E S T I G a C I ó Nunclassified
See 1 more Smart Citation
“…This obser vation lends support for the supposition that an increase in serum IgA might be an antipsoriatic mechanism, stabilizing the psoriatic process. However, although neutrophil chemo taxis inhibiting activity of sera from patients with psoriasis has been shown to depend upon IgA polymeric forms in vitro, it is not clear whether this is important in vivo [19], Different groups have reported that serum IgA levels are increased in psoriasis [8,[20][21][22][23][24], Circulating IgA immune complexes have also been reported to be increased in psori asis [9,25]. Guilhou et al |8| reported that the increase in IgA is specific for psoriasis as no patient with eczema had such an increase.…”
Section: Discussionmentioning
confidence: 99%